Remarks on the Concept of Defects of Consent in Polish and French Law - Dziedzic, Bartłomiej (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The aim of the article is to present the basic principles of the Polish and French law which determined the regulation of defects of consent in each of the legal orders. Firstly, the views of both systems on the concept of declaration of will, without which it is impossible to understand the construction of defects of consent, are presented. Next, the concepts of defects of consent adopted by the two systems are presented: normative in Polish law and psychological in French. The values protected by the construction of defects of consent are also identified and discussed. The general differences between the two systems in terms of the code regulation of such defects are explained. The reason for the consideration of the title issue is the reform of the French law of obligations made by the 2016 ordonnance which also included the regulation of defects of consent. It has been accompanied by a lively discussion that has enriched the body of French academic writings with new statements regarding the regulation of defects of consent.